Healthy high performance : unlocking business success through employee wellbeing - Misra, Monika; Cooper, Cary L. (Routledge, 2025)
"Covid19 and the subsequent lockdowns and changes to working patterns have provided the opportunity to reframe the purpose of health and wellbeing in organisations. Empowering employees to work in ways that optimise their performance, acknowledging both personal and work demands, has opened up possibilities for business that had previously not been considered or even resisted. All savvy organisations will take this as a point in time to rethink HR practice for the benefits of employees and employers. Written by world-renowned expert on wellbeing in organisations, Cary Cooper, and Head of Employee Health and Wellbeing (EMEA) at GlaxoSmithKline, Monika Misra, the book provides clear evidence of what worked well during the lockdowns. They use company, national and international survey results to establish the voice of employees and provide a framework for a three-level response by organisations (including comprehensive wellbeing package), management (including greater communication and mental health support) and employee (building on peer to peer support). This concise book will provide an essential resource to help HR Directors, managers and company leaders use the new ways of working during the Covid19 pandemic to rethink, reboot, reframe and deliver new ways of working for employee wellbeing and improved performance"-- Provided by publisher.
Keywords: Industrial hygiene.; Employee health promotion.; Performance.; Personnel management.; elektronické knihy; electronic books